The Effect of Motivation and Compensation on Employee Performance in South Tangerang - Ilmi, Miftahul; Juliana, Salma (Jurnal Ilmiah Manajemen Kesatuan, 2023)
This research investigates the impact of work motivation and compensation on employee performance in South Tangerang, addressing the critical need for organizations to optimize human resources for strategic goals in a competitive business environment. The study aims to contribute insights into designing effective human resource management strategies that encourage maximum employee contributions, encompassing financial aspects, career development, and recognition of achievements. The hypotheses posited are work motivation influences employee performance, Compensation influences employee performance, work motivation and compensation jointly influence employee performance. Sampling was conducted in various locations in South Tangerang City, Banten, from September to October 2022. The analysis employs SPSS version 22, utilizing a statistical approach to objectively test the proposed hypotheses and obtain measurable results regarding the relationship between workforce motivation, compensation, and employee performance. The findings reveal that work motivation and compensation significantly impact employee performance, as evidenced by low significance values on regression coefficients, indicating a robust positive relationship. The linear regression model demonstrates that approximately 33.5% of the variation in employee performance can be attributed to work motivation and compensation. This research offers a profound understanding of key factors for organizations to enhance productivity and contribution. Recommendations include prioritizing work motivation and ensuring adequate compensation to achieve optimal performance. While acknowledging additional factors influencing employee performance beyond this study's scope, these insights provide valuable guidance for human resource management strategies.